The Role of Woman Workers in Oil Palm Plantation on Family's Economy - Guampe, Feliks Arfid; Kayupa, Olvit Olniwati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
In the beginning, the woman was considered a domestic worker or homemaker. However, along with current development and family economic demands, women have also been involved in public and economic activities. One of the women's choices outside their domestic work is becoming workers in various sectors; one is rural agriculture. This research aimed to examine the role of a woman working on an oil palm farm in a family's economy. This research was conducted in December 2021 and took location in Era village North Mori district North Morowali regency using a qualitative approach with a case study method. The critical informant that has been decided consisted of 6 woman workers. Data analysis uses qualitative descriptive analysis. This research showed that although they work as women on oil palm farms, most still carry out their domestic work by managing their families. On the economic aspect, women work as workers to help their husbands fulfill family economic needs. This research result also showed that most women worker at Era village becomes the most significant contributor to the family's income and economy.